PENERAPAN MODEL PEMBELAJARAN ARTIKULASI DALAM MENINGKATKAN HASIL BELAJAR DI KELAS V SD NEGERI 060935 MEDAN JOHOR - Yanti Elnida Purba; Reflina Sinaga; Juliana; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the improvement of students’ learning outcomes to find out how the learning process was implemented by applying the Articulation learning model on the theme of heat and its transferring at grade 5 of elementary school 060935 Medan Johor in the academic year 2021/2022. The subjects involved 26 students, which consisted of 12 male and 14 female students. The results of the research showed that there was an improvement of students’ learning outcomes on the theme of Heat and Its Transferring at class 5 of elementary school 060935 Medan Johor. It could be seen from the results of research conducted on the pretest that five students who achieved a complete score are 19.23%. Whilst 21 students who achieved incomplete score are 80.77% with an average learning outcome of 52.39. In cycle 1, the post-test increased in which 11 students who have complete score are 42.30%, while 15 students who were incomplete score were 57.70% with an average learning outcome of 68.26. In cycle II, the post-test increased in which 21 students who gained complete score are 80.77%, while five students who achieved incomplete score are 19.23% with an average learning outcome of 84.61. Thus, the conclusion describes that by using the Articulation learning model there is an improvement of students’ learning outcomes on the theme of Heat and Its Transferring at Grade IV of elementary school 060935 Medan Johor in the academic year 2020/2021.